2022
DOI: 10.3390/ani12172243
|View full text |Cite
|
Sign up to set email alerts
|

Using Untargeted LC-MS Metabolomics to Identify the Association of Biomarkers in Cattle Feces with Marbling Standard Longissimus Lumborum

Abstract: Background: To improve the grade of beef marbling has great economic value in the cattle industry since marbling has the traits of high quality and comprehensive nutrition. And because of the marbling’s importance and complexity, it is indispensable to explore marbled beef at multiple levels. This experiment studied the relationship between fecal metabolites and marbling characters, and further screened biomarkers. Results: We performed fecal metabolomics analysis on 30 individuals selected from 100 crossbreed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(70 reference statements)
0
0
0
Order By: Relevance
“…Metabolomic study of Japanese black beef suggested that several metabolites (decanoic acid, uric acid, elaidic acid, 3-phosphoglyceric acid) in meat were potential biomarkers of intramuscular fat to assess marbling levels [ 44 ]. A recent study identified fecal metabolites that influence marbling traits and demonstrated their potential as metabolic biomarkers [ 45 ]. Higher levels of tricarboxylic acid (TCA) cycle (cis-aconitic acid, citric acid, isocitric acid), lipid synthesis (3-hydroxybutiric acid, glycerol 3-phosphate), FA metabolism (o-acetylcarnitine), diabetes (methylhistidine, asymmetric dimethylarginine), and glucose homeostasis (hippuric acid) were found for blood metabolme in Wagyu cattle compared to Holstein [ 46 ].…”
Section: Host and Microbial Metabolome Contribution To Beef Meat Qualitymentioning
confidence: 99%
“…Metabolomic study of Japanese black beef suggested that several metabolites (decanoic acid, uric acid, elaidic acid, 3-phosphoglyceric acid) in meat were potential biomarkers of intramuscular fat to assess marbling levels [ 44 ]. A recent study identified fecal metabolites that influence marbling traits and demonstrated their potential as metabolic biomarkers [ 45 ]. Higher levels of tricarboxylic acid (TCA) cycle (cis-aconitic acid, citric acid, isocitric acid), lipid synthesis (3-hydroxybutiric acid, glycerol 3-phosphate), FA metabolism (o-acetylcarnitine), diabetes (methylhistidine, asymmetric dimethylarginine), and glucose homeostasis (hippuric acid) were found for blood metabolme in Wagyu cattle compared to Holstein [ 46 ].…”
Section: Host and Microbial Metabolome Contribution To Beef Meat Qualitymentioning
confidence: 99%